THE HOAX OF OCEAN ACIDIFICATION - Ollier, Clifford (Quaestiones Geographicae, 2019)
A widespread alarm is sweeping the world at present about the ill effects of man-made increases in carbon dioxide (CO2 ) production. One aspect is that it may cause the ocean to become acid, and dissolve the carbonate skeletons of many living things including shellfish and corals. However, the oceans are not acid, never have been in geological history, and cannot become acid in the future. Changes in atmospheric CO2 cannot produce an acid ocean. Marine life depends on CO2 , and some plants and animals fix it as limestone. Over geological time enormous amounts of CO2 have been sequestered by living things, and today there is far more CO2 in limestones than in the atmosphere or ocean. Carbon dioxide in seawater does not dissolve coral reefs, but is essential to their survival.